Electro-acupuncture for irritable bowel syndrome with constipation: study protocol of a pilot, randomized, double-blinded, sham-controlled trial - Lam, Wai Ching; Chen, Huangyan; Siah, Kewin Tien Ho; Thakur, Elyse R.; Zhong, Linda L. D. (Frontiers in Neurology, 2025)
IntroductionIrritable bowel syndrome with constipation (IBS-C) is a common functional gastrointestinal disorder characterized by constipation, abdominal discomfort, and a substantial impact on patients’ quality of life. While acupuncture could be effective in treating general IBS, high-quality clinical evidence specifically supporting its efficacy in IBS-C remains limited. Our study aims to address this gap by evaluating the effectiveness and safety of electro-acupuncture in managing IBS-C symptoms.MethodsThis a multicentre, randomized, double-blinded, sham-controlled trial. A total of 60 IBS-C patients are randomized to receive either electro-acupuncture (n = 30) or sham acupuncture (n = 30). Patients undergo a 2-week screening period, followed by 6 weeks of treatment (12 sessions) and 6 weeks of follow-up. From the beginning of the screening period to the end of the trial, patients are instructed to complete daily diaries recording bowel movement timing, stool consistency, straining severity, sensation of complete or incomplete evacuation, and the name and dosage of any medications taken. The primary outcome measure follows the FDA-recommended endpoint for IBS-C trials. Additionally, biological samples are collected to explore the potential mechanisms underlying the effects of acupuncture on IBS-C pathology.Ethics and disseminationThe protocol (version 1.4.4) has received approval from the Institutional Review Board of Nanyang Technological University (IRB-2023-451).Trial registration numberNCT06219707.